Current aspects of ear preference - Reiss, M (Folia phoniatrica et logopaedica, 1998)
Sensory asymmetries are most prominent with respect to the eyes and ears. There are various ways to investigate these asymmetries. The tests used for this purpose can be classified as preference, performance and sensory tests. Contrary to eyedness, earedness has received little attention. The objective of this study is to provide a few new investigatory aspects. We were able to identify 13 different tests for the determination of earedness in the literature: 'drawer', 'tablecloth', 'box', 'stop watch', 'telephone receiver', 'wall phone', 'earphone', 'door', 'heartbeat', 'transistor radio', 'voice', 'wall' and 'head movement'. A study including 300 student test subjects was done to determine the usefulness of this battery of 13 tests. A high correlation was found between 'stop watch', 'heartbeat', 'door' and 'box', but not between telephoning and earedness. The determination of earedness by a battery comprised of 4 tests ('stop watch', 'heartbeat', 'door' and 'box') is suggested.